2002
DOI: 10.1123/jtpe.22.1.69
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Cooperative Learning in an Elementary Physical Education Program

Abstract: The purpose of this study was to explore (a) a teacher’s perspective of the implementation of cooperative learning in an elementary physical education program, and (b) the students’ responses to the implementation into their own physical education classes. Data collection included interviews with a physical education teacher and students in two mixed third- and fourth-grade classes and two fourth-grade classes, nonparticipant observation, fieldnotes, a teacher journal, and documents. Inductive analysis and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
0
53

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(183 citation statements)
references
References 30 publications
7
123
0
53
Order By: Relevance
“…Cooperative Learning CL has evolved from three decades of scholarly work in the fields of social relationships, group dynamics, learning, and instruction (Barrett 2005;Dyson 2001Dyson , 2002Gillies 2006;Grineski 1996;Johnson and Johnson 1991;Metzler 2005;Slavin 1996). The ability of CL to accommodate individual differences in the classroom, pupil achievement gains, equity in instruction, and social and personal development contribute to its popularity (Antil et al 1998).…”
Section: Action Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperative Learning CL has evolved from three decades of scholarly work in the fields of social relationships, group dynamics, learning, and instruction (Barrett 2005;Dyson 2001Dyson , 2002Gillies 2006;Grineski 1996;Johnson and Johnson 1991;Metzler 2005;Slavin 1996). The ability of CL to accommodate individual differences in the classroom, pupil achievement gains, equity in instruction, and social and personal development contribute to its popularity (Antil et al 1998).…”
Section: Action Researchmentioning
confidence: 99%
“…In CL small, structured, heterogeneous groups of students are consciously created by the teacher so as to ensure that a full mix of gender, race, ability, and socio-economic background is achieved in every group (Barrett 2005;Dyson 2001Dyson , 2002Dyson and Rubin 2003;Grineski 1996;Johnson and Johnson 1991;Metzler 2005;Slavin 1996). These are not the haphazard teams picked by either teacher or pupil on the spur of the moment to allow competition within a lesson.…”
Section: Action Researchmentioning
confidence: 99%
“…Nevertheless, even though the peer feedback method may have some disadvantages, many studies of physical education, sport and motivation emphasise the benefits of implementing peer feedback and similar methods (e.g. Byra & Marks, 1993;Dyson, 2002;Ernst & Byra, 1998;Johnson, 2004;Johnson & Ward, 2001;Mosston & Ashworth, 2008).…”
Section: Peer Feedback and Pedagogical Challengesmentioning
confidence: 99%
“…This study is supported by other investigations of peer support and motivational climate in physical activity that have been conducted in school PE settings (e.g., Jõesaar, Hein, & Hagger, 2011;Murcia et al, 2008), indicating that peer support as feedback in PE can positively influence students' motivation for the subject. In another study, where peer feedback was a part of collaborative learning, Dyson (2002) followed third and fourth grade students in PE for two years. He found that peer feedback not only had a positive influence on the students' learning of basic skills, but that it also enhanced the students' ability to analyse and reflect on their own and their peers' achieved skills.…”
Section: Peer Feedback In Physical Educationmentioning
confidence: 99%
“…De acuerdo con las ideas previas, el zeitgeist pedagógico en el ámbito de la educación física ha provocado que en la mayoría de los casos se hayan promocionado los entornos colaborativos como la mejor solución a los problemas que la actividad docente puede presentar (Barrett, 2005;Dyson, 2001Dyson, , 2002Dyson y Grineski, 2001;Orlick, 1978aOrlick, , 1978bOrlick, , 1988Orlick, , 2006Polvi y Telama, 2000) más allá de las preferencias personales de los profesores, preferencias de las cuales existe una escasa investigación hasta la fecha, desconociendo si los profesores son preferentemente cooperativos o competitivos en sus entornos laborales, o por el contrario son más individualistas o afiliativos. La idea predominante ha sido destacar las bondades de un entorno cooperativo frente al competitivo o el individualista, ya que con ello se conseguirían mejores resultados en las clases (Dyson y Strachan, 2000).…”
unclassified